Scrutinizing The Local Culture Of Tada Hera Customary Fine In Solving Problems To Avoid Social Disparity In Sikka Regency - Genoveva Dua Eni; Mansur S (Dinasti International Journal of Education Management And Social Science, 2024)
This research analyzed Tada Hera’s customary fines for offenders who cause damage. Each type of offense had its customary fine. This research took place in Sikka Regency. This research aimed to scrutinize the meaning of Tada Hera customary fines to avoid social disparities that occur in the community and to maintain the cultural identity and customary values of the community inherited by the ancestors. The sources of information for this research were regional leaders, customary elders, and community leaders who resided in the Sikka Regency. Data collection techniques were observation and interview. The research data collected was analyzed descriptively using qualitative data analysis techniques. The appropriate method in qualitative research was the ethnographic method. The sanctions given to the perpetrators were advice and also customary fines. Tada Hera customary fines included horse, pig, gold, money, rice, sarong, clothes, and local alcoholic drink. The items were given to the aggrieved person and some were cooked to be eaten at the Tada Hera venue. This research provided deep insight into the dynamics of dispute resolution for the development of policies that were more inclusive and in favor of the community. Thus, the gap that occurred between the victims, perpetrators, and the community.